Lab in the slum. Reassembling methods, institutions, spaces, and identities in Rosario, Argentina - Gabriela Bortz (Tapuya, 2025)
How to invent methodologies with scarce resources to face structural poverty? This paper narrates a journey of discomfort and displacement, forging unexplored trails and seeking meaning in a process of knowledge-making and praxis. It begins with a laboratory set up in a makeshift tent and second-hand equipment in the heart of a precarious neighborhood in Argentina’s third-largest city, aimed to support underserved households lacking formal drinking water services. The project evolved from water quality assessments to encompass broader health initiatives through collaboration with local groups, navigating uncomfortable materialities and institutionalities along the way. Drawing on a qualitative case study and an action research involvement spanning over a decade, this work integrates theoretical discussions on transformative research practices and methodologies. It examines how unconventional approaches challenge mainstream scientific trajectories, emphasizing fluidity in technological reinvention, its impact on identities and relationships, and boundary unmaking. The study highlights the transformative potential of “messing with methods,” subverting scientific norms and shaping ethical, community-centered practices, and the triple agency of precarity as a trigger, constraint, and epistemic unsettlement. By reassembling methods and identities within resource-constrained contexts, the project illuminates the dynamic interplay between knowledge-making and societal engagement, redefining boundaries between research, community, and policy spheres.